Metal Catalyst-Free One-pot Synthesis of Carboxamide Derivatives via Ugi-4CC Reaction and Its Anti-tubercular Study - Gondaliya, Bhumit L.; Sriram, Dharmarajan; Varakala, Saiprasad D.; Dholaria, Piyush V.; Dhuda, Gautam K.; Kapadiya, Khushal M. (Letters in Drug Design & Discovery, 2024)
Background: A new series of ten composites with sulphur based carboxylic acid and benzylamine were synthesized by Ugi 4-components reaction (Ugi-4CR) and screened for antituberculosis activity against the Mycobacterium tuberculosis H37Rv strain.Objective: Target compounds were isolated, purified, identified, and characterized by MS, FT-IR, 1HNMR, APT, and 13C-NMR then the antituberculosis activity was examined by Microplate Alamar Blue Assay (MABA) method.Methods: This study was based on the articulation of carboxamide linkage bearing S-linkage in the core unit by reacting four different units, i.e., 2-(pyrimidin-2-ylthio)acetic acid, aromatic aldehyde, benzylamine and tertiary butyl isocyanide at RT in an atom economy route of synthesis. The desired product (5a- 5j) was synthesized via one-pot and Metal-free conditions.Results: Compounds (5a-5j) synthesized in good yields and compared to MIC values of Isoniazid 0.05 (μg/mL), Rifampicin 0.1 (μm/mL), and Ethambutol 1.56 (μg/mL) as a positive control.Conclusion: Synthesized compounds give excellent yield. Among the ten derivatives, compound 5f has comparable antituberculosis activity.
Keywords: linkage